Computer Graphics of the Regular Polygons and their Applications - Villacís, César; Fuertes, Walter; Zambrano, Margarita; Cabascango, Carlos; Cuichán, Edwin; Benavides, Ramiro; Solís, Fernando; Kostikova, Margarita (KnE Engineering, 2018)
The computer graphics of regular polygons and their applications is a scarcely studied area that allows to create situations of significant learning by its mathematical and geometric content. This research presents the design and programming of regular polygons and composite sacred figures using computational analytical geometry and development tools such as C#, GDI+ graphics engine and Java with SWING graphical interface. In order to achieve this, the Agile Extreme Programming (XP) methodology has been used to translate computer graphics software applications, with the purpose of understanding how computer graphics work to generate combinations of geometric figures based on regular polygons, fully parameterizable. The proof of concept, which included the evaluation of the application performance in both the .NET framework and the NetBeans IDE were carried out with a student’s group of engineering in Computer Graphics subject.